Efficacy of Air-abrasion Technique and Additional Surface Treatment at Titanium/Resin Cement Interface - Fonseca, Renata Garcia [UNESP]; Haneda, Isabella Gagliardi [UNESP]; de Almeida-Junior, Antonio Alves [UNESP]; Abi-Rached, Filipe de Oliveira [UNESP]; Adabo, Gelson Luis [UNESP] (Quintessence Publishing Co Inc, 2012)
Purpose: To evaluate the effect of surface treatments on the shear bond strength (SBS) of a resin cement to commercially pure titanium (CP Ti).Materials and Methods: Two hundred cast CP Ti disks were divided into 5 groups (n = 40), which were treated with one of the following air-abrasion techniques: (1) 50-mu m Al2O3 particles; (2) 120-mu m Al2O3 particles; (3) 250-mu m Al2O3 particles; (4) 30-mu m silica-modified Al2O3 particles (Cojet Sand); (5) 50-mu m Al2O3 particles followed by 110-mu m silica-modified Al2O3 particles (Rocatec Plus). For each air-abrasion technique, the following additional surface treatments were used (n = 10): (1) none; (2) adhesive Adper Single Bond 2; (3) silane RelyX Ceramic Primer; (4) silane plus adhesive. RelyX ARC resin cement was bonded to CP Ti surfaces. All specimens were thermocycled (5,000 cycles) before being tested in shear mode. Data (MPa) were analyzed using two-way ANOVA and Tukey's test (alpha = 0.05). Failure mode was determined with a stereomicroscope (20X).Results: The results revealed that the air-abrasion technique (p < 0.001), additional surface treatment (p < 0.001) and their interaction were significant (p < 0.001). Except for the 50-mu m Al2O3 + adhesive group, 250-mu m Al2O3 particles promoted significantly higher SBS than 50-mu m Al2O3 particles (p < 0.001), while Rocatec Plus provided bond strengths that were similar to or higher than those of Cojet Sand. of the additional surface treatments, the adhesive provided the best results in combination with the 3 air-abrasion techniques (50-mu m, 120-mu m, and 250-mu m Al2O3), whereas in the groups abraded with silica-modified Al2O3 particles (Cojet Sand and Rocatec Plus), the best results were obtained with additional silane. The two combinations that promoted the highest SBS were 250-mu m Al2O3 + adhesive and Rocatec Plus + silane. All groups showed 100% adhesive failure.Conclusion: The selection of the best additional surface treatment varied according to the air-abrasion technique. Particle size was the decisive factor in determining the bond strength when micromechanical retention was the only bonding mechanism. When both mechanisms were present, in addition to particle size, the material applied as the additional surface treatment also contributed to determining the bond strength.
Keywords: resin cement; titanium; surface treatment; air abrasion; silica coating